2020
DOI: 10.1088/1755-1315/425/1/012003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of probiotic supplementation in rations containing leubiem fish waste (Chanthidermis maculatus) on the performance of local ducks

Abstract: The aim of this study is to determine the effect of probiotic supplementation in rations containing leubiem fish waste (Chanthidermis Maculatus) on the performance of local duck. The study used 192 female local ducks 8-20 weeks old grower phase. The ducks were allocated into 4 treatments and 4 replications (12 ducks/pen). The female local ducks was fed ration contained 18% crude protein and 2700 kcal/kg metabolizable energy. The experiment used completely randomized design with 4 treatment rations: P1 (basal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…Kadar protein kasar yang terdapat pada limbah ikan leubiem berpotensi digunakan sebagai sumber protein dalam formulasi ransum guna meningkatkan pertumbuhan atau produktivitas itik petelur. Beberapa hasil penelitian sebelumnya menunjukkan bahwa penggunaan limbah ikan leubiem (Chanthidermis maculatus) sebagai bahan pakan dalam formulasi ransum itik lokal dapat memberi respon positif terhadap performan dan persentase karkas itik lokal jantan umur 16 minggu, serta meningkatkan kinerja pertumbuhan itik lokal umur 8-20 minggu [3,4].…”
unclassified
“…Kadar protein kasar yang terdapat pada limbah ikan leubiem berpotensi digunakan sebagai sumber protein dalam formulasi ransum guna meningkatkan pertumbuhan atau produktivitas itik petelur. Beberapa hasil penelitian sebelumnya menunjukkan bahwa penggunaan limbah ikan leubiem (Chanthidermis maculatus) sebagai bahan pakan dalam formulasi ransum itik lokal dapat memberi respon positif terhadap performan dan persentase karkas itik lokal jantan umur 16 minggu, serta meningkatkan kinerja pertumbuhan itik lokal umur 8-20 minggu [3,4].…”
unclassified
“…It was necessary to measure diet conversion and efficiency related to its ability to support growth and production of boiler chickens determining the nutritional benefits of fermented diet containing magot flour, probiotics and digestive enzymes. [17] stated that chicken diet that was consumed, digested and absorbed properly resulted in low conversion value and high diet efficiency compared to diet that does not meet quality requirements. The lowest level of diet conversion value indicated that the amount of diet that can be converted into production value in poultry is higher which indicated the level of quality of the diet consumed of broilers.…”
Section: Feed Conversion and Efficiencymentioning
confidence: 99%
“…Additionally, this shows that leubiem fish waste can serve as a reliable feed ingredient and also a source of adequate nutrition in formulating duck rations. Similarly, probiotic supplementation serves as an antibacterial to maintain the health status of ducks [2].…”
Section: Mortalitymentioning
confidence: 99%
“…Optimizing the use of local feed ingredients is one of the methods to reduce the costs of duck farming without hampering livestock productivity [2]. One of the local feed ingredients used in Peking duck rations is fish waste.…”
Section: Introductionmentioning
confidence: 99%